2018
DOI: 10.2147/ijn.s170305
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory properties of graphene oxide for osteogenesis and angiogenesis

Abstract: BackgroundThe osteo-immunomodulatory properties of biomaterials play an important role in the outcomes of bone regeneration. Graphene oxide (GO) has been widely applied in many research fields due to its unique properties. However, the immunomodulatory properties of GO as a biomaterial for bone tissue engineering are still unclear.Materials and methodsIn this study, we evaluated the Inflammatory response of RAW264.7 cells influenced by GO. Then the osteogenic differentiation of BMSCs, and angiogenic differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 37 publications
1
52
0
Order By: Relevance
“…This would match with our observed results after the exposure to GNPs. Taken together, our overall results after GO/GNP exposure do not show an inflammatory response in the Caco-2/HT29 coculture, which would support their potential use as promising biomaterials for bone tissue engineering, by inducing a beneficial immunomodulatory bone environment 51 .…”
Section: Discussionsupporting
confidence: 72%
“…This would match with our observed results after the exposure to GNPs. Taken together, our overall results after GO/GNP exposure do not show an inflammatory response in the Caco-2/HT29 coculture, which would support their potential use as promising biomaterials for bone tissue engineering, by inducing a beneficial immunomodulatory bone environment 51 .…”
Section: Discussionsupporting
confidence: 72%
“…Subsequently, the immune microenvironment could stimulate stem cells to differentiate into osteoblasts. For example, Xue et al 157 studied the effect of GO on the inflammatory response of mouse macrophage line RAW-264.7 cells and found that the expression of proinflammatory cytokines IL-6, IL-1 β, Interferon γ (IFN-γ), Oncostatin M (OSM) and TNFα was up-regulated in RAW 264.7 cells treated with GO. Subsequently, they used the supernatant of GO/RAW 264.7 as the conditioned medium to culture BMSCs, the results of which showed that the expressions of myeloiddifferentia-tionfactor88 (MYD88), BMP2, vascular endothelial growth factor (VEGF) and OSM of BMSCs were up-regulated in this conditioned medium, indicating that GO stimulation was beneficial to the formation of immune microenvironment of BMSCs osteogenesis.…”
Section: Immunomodulatory Mechanism Of Gds-induced Bone Regenerationmentioning
confidence: 99%
“…When cultured with mouse macrophages, GO induced the formation of a beneficial osteoimmunomodulatory environment which caused osteogenic differentiation of BMSCs, stimulated the upregulation of vascularrelated receptors in human umbilical vein endothelial cells, and promoted their tube formation in vitro. 172 Immunomodulatory biomaterials can be categorized into four separate classes based on their methods of, respectively, action and activation. (a) Phenotypic switch of the cells of the immune system (predominantly macrophages) from a destructive inflammatory phenotype to a constructive regenerative phenotype, (b) exogenous surface coatings, (c) innate material properties, and (d) direct activation of stem cell-mediated regeneration.…”
Section: Immune-modulatory Materials For Bone Regenerationmentioning
confidence: 99%
“… 171 Indeed, researchers have begun using biomaterials that activate immunomodulation to “trick” the body into repairing itself. For example, Xue et al, 172 demonstrated that GO can be a biomaterial with immunomodulatory capabilities. When cultured with mouse macrophages, GO induced the formation of a beneficial osteo-immunomodulatory environment which caused osteogenic differentiation of BMSCs, stimulated the upregulation of vascular-related receptors in human umbilical vein endothelial cells, and promoted their tube formation in vitro.…”
Section: Immune-modulatory Materials For Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation